Data mining and medical knowledge management : cases and applications - Berka, Petr.; Rauch, Jan.; Zighed, Djamel A., 1955- (Hershey, PA : Information Science Reference, 2009)
"This book presents 20 case studies on applications of various modern data mining methods in several important areas of medicine, covering classical data mining methods, elaborated approaches related to mining in EEG and ECG data, and methods related to mining in genetic data"--Provisto por el editor.
Incluye referencias bibliográficas e índice.
Keywords: Minería de datos; Medicina; Estudios de casos